Mediterranean Diet and Overactive Bladder - Bozkurt, Yunus Erol; Temeltaş, Gökhan; Müezzinoğlu, Talha; Üçer, Oktay (International neurourology journal, 2022)
Purpose: The relationship between nutrition and overactive bladder (OAB) has yet to be elucidated. Therefore, this study investigated the relationship between the Mediterranean diet and OAB.Methods: The 14-item Mediterranean Diet Adherence Screener (MeDAS) and Overactive Bladder-Validated 8-question Screener (OAB-V8), validated in Turkish, were administered to 500 patients over the age of 18 who presented to outpatient clinics other than urology outpatient clinics. Of those patients, 174 with chronic diseases and urinary tract infections (based on urinalysis and a detailed medical history) were excluded. Therefore, 326 patients’ data were analyzed.Results: There was a negative correlation between the MeDAS and OAB-V8 scores. High OAB-V8 scores were associated with obesity (body mass index ≥30 kg/m2), being single, and a low education level.Conclusions: Dietary patterns represent a broader perspective on food and nutrient consumption and may therefore be more predictive of disease risk. The Mediterranean type should be recommended in the first-line treatment of patients with OAB symptoms. It is easily possible to determine the compliance of patients with this diet by using the 14-item MeDAS.